2014
DOI: 10.7314/apjcp.2014.15.2.899
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine And Cisplatin Followed by Chemo-Radiation for Advanced Nasopharyngeal Carcinoma

Abstract: Concurrent chemo-radiation (CRT) has been established as the standard of care for non-metastatic locoregionally advanced nasopharyngeal carcinoma (NPC) but recently the addition of induction chemotherapy in the already established regimen has presented an attractive multidisciplinary approach. This retrospective study was carried out to evaluate the efficacy of induction chemotherapy (IC) followed by CRT for the management of loco-regionally advanced NPC. Between July 2005 and September 2010, 99 patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
1
10
1
Order By: Relevance
“…NPC was also sensitive to chemotherapy, whether dose-dense chemotherapy could bring the same clinical benefit as patients with breast cancer? Our study showed that the CR rate was 19.2% after dose-dense chemotherapy, which was higher than 15% reported by Jamshed (2014), and was significantly higher than that (3.9%) of traditional chemotherapy. The rate of CR (3.9%) and PR (53.0%) in control group was similar with 4.3% and 51.7% reported by Zeng (2014).…”
Section: Discussioncontrasting
confidence: 73%
“…NPC was also sensitive to chemotherapy, whether dose-dense chemotherapy could bring the same clinical benefit as patients with breast cancer? Our study showed that the CR rate was 19.2% after dose-dense chemotherapy, which was higher than 15% reported by Jamshed (2014), and was significantly higher than that (3.9%) of traditional chemotherapy. The rate of CR (3.9%) and PR (53.0%) in control group was similar with 4.3% and 51.7% reported by Zeng (2014).…”
Section: Discussioncontrasting
confidence: 73%
“…Jamshed and colleagues in their study on treatment of locoregionally advanced nasopharyngeal carcinoma have used Gemcitabine and Cisplatin as induction chemotherapy. They have shown that 15% of patients had complete response after induction chemotherapy with good patient compliance and acceptable toxicity [ 19 ]. In the present study Gemcitabine was given in combination with Cisplatin as induction chemotherapeutic drug, which showed complete response in 18% patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the unique mechanism of Hsp90 inhibitors has been the ideal medicine against cancer or virus. Some researchers concluded that combination of chemotherapy drug and chemo-radiation was a safe and effective regimen in management of cancer, meriting further investigation in randomized clinical trials (Jamshed et al, 2014). LDM in our research was a radiomimetic enediyne anticancer drug and showed great effect in combination with Hsp90 inhibitor which was also a good selection in the drug combination.…”
Section: Discussionmentioning
confidence: 97%